A comparison between the influence of nanoclay and isocyanate on urea-glyoxal resins. (2nd January 2018) - Younesi-Kordkheili, Hamed; Pizzi, Antonio
ABSTRACT: The effects of pMDI and nanoclay on physical and mechanical properties of particleboards bonded with a urea-glyoxal (UG) resin were compared. pMDI (4, 6 and 8%) and nanoclay (1, 2 and 3%) were added to the synthesised UG resin. The properties of the resins prepared as well as of the particleboard panels bonded with them were then measured. The gel time shortened and the viscosity increased by addition of both pMDI and nanoclay into a UG resin. Differential Scanning Calorimetry (DSC) showed that the addition of pMDI decreased the onset, curing and peak temperatures of the UG resin. Nanoclay instead, only decreased the peak temperature of the UG resin. The particleboards bonded with UG resins/isocyanate yielded lower water absorption and percentage thickness swelling when compared to those bonded with the UG resin/nanoclay and the control UG resins. The mechanical properties of the particleboards bonded with UG resins could be significantly improved by the addition of increasing percentages of nanoclay and pMDI. The panels where pMDI was added to the UG resin presented higher flexural modulus, flexural strength and IB strength compared to those bonded with UG resins containing nanoclay.